Post-Sterilization Physicochemical Characterization and Biological Activity of Cellulose Nanocrystals Coated with PDDA - Ashley Donato; Siddharth Nadkarni; Lakshay Tiwari; Serafina Poran; Rajesh Sunasee; Karina Ckless (Molecules)
The rapid expansion of medical nanotechnology has significantly broadened the potential applications of cellulose nanocrystals (CNCs). While CNCs were initially developed for drug delivery, they are now being investigated for a range of advanced biomedical applications. As these applications evolve, it becomes crucial to understand the physicochemical behavior of CNCs in biologically relevant media to optimize their design and ensure biocompatibility. Functionalized CNCs can adsorb biomolecules, forming a “protein corona” that can impact their physicochemical properties, including alterations in particle size, zeta potential, and overall functionality. In this study, CNCs were coated with low (8500 Da)- and high (400,000–500,000 Da)-molecular-weight cationic polymer (poly(diallyldimethylammonium chloride—(PDDA) via non-covalent grafting, and their physicochemical characteristics, as well as their biological effects, were assessed in physiologically relevant media after sterilization. Our findings show that autoclaving significantly alters the physicochemical properties of CNC-PDDA, particularly when coated with low-molecular-weight (LMW) polymer. Furthermore, we observed that CNC-PDDA of a high molecular weight (HMW) has a greater impact on cell viability and blood biocompatibility than its LMW counterpart. Moreover, cellular immune responses to both CNC-PDDA LMW and HMW vary in the presence or absence of serum, implying that protein adsorption influences cell-nanomaterial recognition and their biological activity. This study provides valuable insights for optimizing CNC-based nanomaterials for therapeutic applications.